Diseño de un mecanismo robótico bípedo antropomórfico validado por señales biomecánicas (2025)
Humanoid robots are multi-jointed systems that feature two legs for locomotion and two arms for manipulation, and are considered ideal for collaborating with humans in operating environments compatible with human tools. Notable examples of humanoid robots include HUBO, Atlas, Asimo, HRP, and Schaft. [1] Initially, these robots were designed for structured and constrained environments; however, the need to perform tasks in unstructured and hazardous environments, such as in disasters, has driven research into more advanced hardware and control algorithms.